Biophysical and biochemical evidence for the role of acetate kinases (AckAs) in an acetogenic pathway in pathogenic spirochetes. - Ranjit K Deka; Shih-Chia Tso; Wei Z Liu; Chad A Brautigam (PLoS ONE)
Unraveling the metabolism of Treponema pallidum is a key component to understanding the pathogenesis of the human disease that it causes, syphilis. For decades, it was assumed that glucose was the sole carbon/energy source for this parasitic spirochete. But the lack of citric-acid-cycle enzymes suggested that alternative sources could be utilized, especially in microaerophilic host environments where glycolysis should not be robust. Recent bioinformatic, biophysical, and biochemical evidence supports the existence of an acetogenic energy-conservation pathway in T. pallidum and related treponemal species. In this hypothetical pathway, exogenous D-lactate can be utilized by the bacterium as an alternative energy source. Herein, we examined the final enzyme in this pathway, acetate kinase (named TP0476), which ostensibly catalyzes the generation of ATP from ADP and acetyl-phosphate. We found that TP0476 was able to carry out this reaction, but the protein was not suitable for biophysical and structural characterization. We thus performed additional studies on the homologous enzyme (75% amino-acid sequence identity) from the oral pathogen Treponema vincentii, TV0924. This protein also exhibited acetate kinase activity, and it was amenable to structural and biophysical studies. We established that the enzyme exists as a dimer in solution, and then determined its crystal structure at a resolution of 1.36 Å, showing that the protein has a similar fold to other known acetate kinases. Mutation of residues in the putative active site drastically altered its enzymatic activity. A second crystal structure of TV0924 in the presence of AMP (at 1.3 Å resolution) provided insight into the binding of one of the enzyme's substrates. On balance, this evidence strongly supported the roles of TP0476 and TV0924 as acetate kinases, reinforcing the hypothesis of an acetogenic pathway in pathogenic treponemes.